Explaining Observed Daily Variations and Decadal Trends in the Diurnal Air Temperature Range - Sarosh Alam Ghausi; Kaighin McColl; Erwin Zehe; Axel Kleidon (Geophysical Research Letters, 2025)
Abstract Understanding variability and trends in the near‐surface diurnal air temperature range (DTR) remains unclear due to its complex interactions with antecedent radiative and hydrologic conditions. Here, we use a thermodynamic systems approach, and show that DTR primarily reflects changes in lower atmospheric heat storage, governed by diurnally constrained non‐latent energy input from the surface into the atmospheric boundary layer. This approach predicts DTR across a range of climates, reproduces its day‐to‐day variations, and explains its decline with rising greenhouse gas (GHG) concentrations. We show that in addition to strong controls exerted by radiation and cloud cover, DTR carries imprints of surface water stress during the water‐limited evaporative regime. Our expression yields a mean reduction of 0.23°C in DTR per 1°C rise in temperatures, in response to changes in GHG forcings. Our findings imply that the first‐order decline in DTR with global warming can be explained by increased GHG forcings alone.